Immunogenicity of PCV24, an expanded pneumococcal conjugate vaccine, in adult monkeys and protection in mice. Issue 30 (5th July 2021) - McGuinness, Debra; Kaufhold, Robin M.; McHugh, Patrick M.; Winters, Michael A; Smith, William J.; Giovarelli, Cecilia; He, Jian; Zhang, Yuhua; Musey, Luwy; Skinner, Julie M.
Highlights: Twenty-four serotypes are conjugated to CRM197. PCV24 is immunogenic and induces a functional antibody response in adult monkeys for vaccine serotypes. PCV24 provides similar immunogenicity as the lower valent vaccines in adult monkeys. PCV24 provides protection against pneumococcal infection in a mouse challenge model. Abstract: Invasive pneumococcal disease (IPD) is responsible for serious illnesses such as bacteremia, sepsis, meningitis, and pneumonia in young children, older adults, and persons with immunocompromising conditions and often leads to death. Although the most recent pneumococcal conjugate vaccines (PCVs) have been designed to target serotypes identified as the primary causative agents of IPD, the epidemiological landscape continues to change stressing the need to develop new PCVs. We have developed an investigational 24-valent PCV (PCV24) including serotypes 1, 2, 3, 4, 5, 6A, 6B, 7F, 8, 9N, 9V, 10A, 11A, 12F, 14, 15B, 17F, 18C, 19A, 19F, 20, 22F, 23F, and 33F all conjugated to CRM197 and evaluated this vaccine in adult monkeys. PCV24 was shown to be immunogenic and induced functional antibody for all vaccine serotypes. Of the serotypes common to PCV13 and V114 (PCV15), PCV24 had a similar immunogenic response with the exceptions of 23F which had higher IgG GMCs for PCV13 and V114, and 7F which had higher GMCs for PCV13. Functional antibody responses were similar for the serotypes in common between PCV24, PCV13 and V114 vaccines, with the exception of serotype 7F which was greater for PCV13. Overall, this study shows that PCV24 provided similar immunogenicity as the lower valent vaccines in adult monkeys with no apparent serotype interference. In addition, PCV24 also provided protection against pneumococcal infection in a mouse challenge model.